PEGylation of cationic liposomes encapsulating soluble Leishmania antigens reduces the adjuvant efficacy of liposomes in murine model. (6th October 2017) - Naseri, H.; Eskandari, F.; Jaafari, M. R.; Khamesipour, A.; Abbasi, A.; Badiee, A.
Summary: Although there have been several attempts to develop a vaccine against leishmaniasis, no vaccine in human has been developed yet. Liposomes consisting of 1, 2‐dioleoyl‐3‐trimethylammonium‐propane (DOTAP) encapsulating soluble Leishmania antigens (SLA) enhance protective immunity of SLA against Leishmania major infection in mice. However, they immobilized at the injection site because of their positive charge. To overcome the problem, shielding the surface charge with polyethylene glycol (PEGylation) was chosen in this study. Liposomal SLA consisting different concentrations of PEG (1.9%‐15% mol) were prepared. BALB/c mice were immunized three times in 3 weeks intervals with different formulations. Lesion development and parasite burden in footpad and spleen were evaluated to specify the type of generated immune response and extent of protection. Th1/Th2 cytokine profiles and IgG isotypes were also analysed. The maximum protection was observed in mice immunized with Lip‐SLA or pLip‐SLA (1.9%) due to smaller footpad swelling, reduction in parasite load, an increase in IgG2a and IFN‐γ production. Our results showed that immunization of mice with a high level of PEG (>7.5%) did not improve protective immunity of liposomal SLA. The presence of PEG, particularly more than 3.75%, is not recommended for protection against leishmaniasis.